Investigation and Study of Angiotensin-converting Enzyme (ACE) Gene Polymorphism in Iranian Women with Recurrent Pregnancy Loss (RPL) - Morteza Bagheri; Isa Abdi Rad; Fariba Nanbaksh (Medicine and Medical Research: New Perspectives Vol. 8, 2024)
Recurrent Pregnancy Loss (RPL) is multifactorial, and several genetic and environmental risk factors that influence the balance between fibrinolysis and coagulation pathways play a central role in the outcome of conception. A large body of studies demonstrates that genes associated with angiogenesis such as vascular endothelial growth factor (VEGF) and nitric oxide synthase (NOS), Thrombogenesis such as angiotensin I-converting enzyme (ACE), methylenetetrahydrofolate reductase (MTHFR) C677T, Factor V (FV) G1691A, Factor II (FII) G20210A, and plasminogen activator inhibitor-1 (PAI-1) 5G/4G, and immune-related genes such as SERPINA4, FAU, HLA-DQ2/DQ8, HLA-C, Natural killer cells (NKs) and B Cells and other genetic variations are associated with RPL by different mechanisms. ACE as a key modulator of the Renin-angiotensin-aldosterone system (RAAS) affects homeostasis. RAAS results in thrombophilia, preeclampsia, RPL and infertility through the fibrinolytic pathway with unclear mechanisms. The ACE DD genotype causes high production of angiotensin II from angiotensin I, which is associated with an increased level of circulating PAI-1. The high production of PAI-1 leads to the inhibition of fibrinolysis. This study aimed to determine the allele and genotype frequencies of the angiotensin-converting enzyme (ACE) gene in Iranian women with unexplained RPL. Fifty patients with RPL and 63 fertile healthy women as controls were included in the study. Genomic DNA was extracted by a standard salting-out method. All genotypes were determined using PCR. The analysis showed that patient (x2 = 0.347, p = 0.84) and control (x2 = 0.77, p = 0.68) groups fitted the Hardy–Weinberg equilibrium strongly. No significant differences were found regarding the frequencies of ACE genotypes [deletion/deletion (D/D), insertion/deletion (I/D) and insertion/insertion (I/I)] and alleles between cases and controls. Based on these findings, we could not find any association between ACE (D/D, I/D and I/I) gene polymorphisms and RPL. Evaluating the Factor V Leiden G1691A and Prothrombin Gene G20210A Mutations in combination with environmental factors must be considered.